EMERGENCE OF GRASSY HABITATS DURING THE GREENHOUSE–ICEHOUSE SYSTEMS TRANSITION IN THE MIDDLE EOCENE OF SOUTHERN SOUTH AMERICA (Ameghiniana, 2018)
Phytolith assemblages recovered from the middle Eocene Koluel-Kaike Formation in Central Patagonia, southern South America, confirm the presence of herbaceous components, mainly related to mixed ecosystems or savannahs, and subordinate forest communities. This new palaeobotanical information reveals a clear transition between previously described woodland-dominated communities from the early Eocene Las Flores Formation, and grass-rich ecosystems from the mid-Eocene Sarmiento Formation. The early appearance of grass-dominated ecosystems in southern South America, would be related to the worldwide greenhouse to icehouse systems transition initiated during the mid-Palaeogene.